The Belissariotai family: a contribution to Byzantine prosopography - Papadopulos, Alexandros (Byzantinische Zeitschrift, 2022)
Michael and Niketas Choniates, significant figures of letters of the second half of the twelfth and the early thirteenth century, were closely related to the Belissariotai, a noble family of the Byzantine aristocracy. Thanks to both Choniatai brothers we are able to gather valuable information about the Belissariotai and to examine not only their role in the administration of the state during the last quarter of the twelfth century, but also their unbreakable bonds of friendship and kinship with the Choniatai. This paper aims to present a thorough prosopographic study on the Belissariotai family through the examination of literary and sigillographic evidence and to challenge a series of long-established views regarding the different stages of their life and career.